2022
DOI: 10.1080/02670836.2022.2077541
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on friction stir welding of tailor weld blanks

Abstract: The effect of single-pass (SP) and double-pass (DP) friction stir welding (FSW) on metallographic and mechanical properties of joints was investigated in this study. Uniform temperature distribution across the weld cross-section was obtained during double-pass FSW (DP-FSW). SEM and EDS analyses showed an increase in the fraction of second phase particles (SPPs) and the formation of new SPPs by DP-FSW. An increase in hardness values by 13.3% and a severe decrease in joint efficiency by 46.7% were observed by DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…From Figure 15(g) and (h), it can be seen the Al part shows an anodic behavior with intergranular corrosion along with pitting in both samples S1 and S2. Previous research 75,76 has indicated that finer grains exhibit an increased amount of grain boundaries, leading to a decrease in the strength of the galvanic couple formed between the core and the surface. Consequently, specimens with finer grains exhibit improved corrosion resistance.…”
Section: Electrochemical Characterization Of Welded Jointsmentioning
confidence: 99%
“…From Figure 15(g) and (h), it can be seen the Al part shows an anodic behavior with intergranular corrosion along with pitting in both samples S1 and S2. Previous research 75,76 has indicated that finer grains exhibit an increased amount of grain boundaries, leading to a decrease in the strength of the galvanic couple formed between the core and the surface. Consequently, specimens with finer grains exhibit improved corrosion resistance.…”
Section: Electrochemical Characterization Of Welded Jointsmentioning
confidence: 99%